Toleration, power and the right to justification : Rainer Forst in dialogue - Forst, Rainer, 1964- (Book collections on Project MUSE., 2020)
This volume introduces Rainer Forst's critical theory of toleration, offering a development of his major work Toleration in Conflict with critical engagement from a range of outstanding interlocutors, including Chandran Kukathas, Melissa S. Williams and Patchen Markell.